Why is Voluntary Financial Education so Unpopular? Experimental Evidence from Mexico - Bruhn, Miriam (The World Bank, 2013)
Take-up of voluntary financial education programs is typically extremely low. This paper reports on randomized experiments around a large financial literacy course offered in Mexico City to understand the reasons for low take-up, and to measure the impact of financial education. It documents that the general public displays little interest in such courses and that participation is low even among individuals who express interest in financial education. The paper experimentally investigates barriers to take-up, and finds no impact of relaxing reputational or logistical constraints and no evidence that time inconsistency is the reason for limited participation. Even relatively sizeable monetary incentives get less than 40 percent of interested individuals invited to training to attend. Using a randomized encouragement design, the authors measure the impact of the course on financial knowledge and behavior. Attending training results in a 9 percentage point increase in financial knowledge and a 9 percentage point increase in saving outcomes, but no impact on borrowing behavior. Administrative data indicate that the savings impact is relatively short-lived. The results suggest people are making optimal choices not to attend financial education courses, and point to the limits of using general purpose courses to improve financial behavior for the general population